Direct Conversion of Mono‐ and Polysaccharides into 5‐Hydroxymethylfurfural Using Ionic‐Liquid Mixtures. Issue 16 (27th June 2016) - Siankevich, Sviatlana; Fei, Zhaofu; Scopelliti, Rosario; Jessop, Philip G.; Zhang, Jiaguang; Yan, Ning; Dyson, Paul J.
Abstract: Platform chemicals are usually derived from petrochemical feedstocks. A sustainable alternative commences with lignocellulosic biomass, a renewable feedstock, but one that is highly challenging to process. Ionic liquids (ILs) are able to solubilize biomass and, in the presence of catalysts, convert the biomass into useful platform chemicals. Herein, we demonstrate that mixtures of ILs are powerful systems for the selective catalytic transformation of cellulose into 5‐hydroxymethylfurfural (HMF). Combining ILs with continuous HMF extraction into methyl‐isobutyl ketone or 1, 2‐dimethoxyethane, which form a biphase with the IL mixture, allows the online separation of HMF in high yield. This one‐step process is operated under relatively mild conditions and represents a significant step forward towards sustainable HMF production. Abstract : One step wonder : Cellulose is transformed into 5‐hydroxymethylfurfural (HMF) in high yield in a single step using a CrCl2 catalyst immobilized in a mixture of ionic liquids (ILs). Combining ILs with continuous HMF extraction into methyl‐isobutyl ketone or 1, 2‐dimethoxyethane allows the online separation of HMF in high yield. This one‐step process is operated under relatively mild conditions and represents a significant step forward towards sustainable HMF production.